(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Accurate soil nutrient measurement is vital for modern agriculture as it directly impacts crop yield and quality. By precisely assessing soil nutrient levels, farmers can make well-informed decisions regarding fertilization, irrigation, and other management practices, leading to increased crop yields and improved sustainability. The proposed system utilizes an NPK sensor, DHT11 sensor, and soil moisture sensor to continuously monitor soil conditions in real-time. The collected data, including nutrient levels, temperature, humidity, and moisture, is analyzed and transmitted to a cloud platform (Arduino IoT Cloud.) for remote monitoring. By implementing this IoT solution, farmers can optimize their agricultural practices, enhance crop yields, reduce the usage of chemical fertilizers, and overcome challenges such as labor shortages and limited farming knowledge. Additionally, the proposed system offers the capability to recommend appropriate fertilizer according to the NPK values detected in the soil, providing farmers with accurate information and convenient access to insights through mobile application. This contributes to sustainable and efficient farming practices.